Structure and secretion mechanisms of floral glands in Diplopterys pubipetala (Malpighiaceae), a neotropical species - Fiorilo Possobom, Clivia Carolina [UNESP]; Guimaraes, Elza [UNESP]; Machado, Silvia Rodrigues [UNESP] (Elsevier B.V., 2015)
Detailed studies on the distribution, structure, and secretion activity of floral glands are important to understand the relationship of flowers with oil-collecting bees in Malpighiaceae. Here, we characterised the floral biology and the glands in sepals, petals and connective tissues of Diplopterys pubipetala. The data on the floral biology were obtained under field conditions. The samples from functional flowers were prepared for anatomical, histochemical and ultrastructural studies. The bees of the genera Monoeca and Centris were the most frequent visitors. While both insects searched for oil, the former also collected pollen and connective tissue secretions. The conspicuous and subsessile sepal glands are arranged in pairs on the abaxial surface, presenting structural and cellular machinery typical of epithelial elaiophores. The oil is accumulated in the subcuticular space and released when the bee scraps the cuticle, causing its rupture. The petal glands, observed at the fimbriate edges, are diminutive, comprising secretory epithelium surrounding a central core of parenchymal cells supplied with vascular tissues. The petal glands are typically osmophores, and secretion occurs via diffusion through the thin cuticle. The glandular connective comprises large globular secretory epithelial cells, which produce a bright and viscous secretion, mimicking pollen grains. This predominantly hydrophilic secretion is released to the surface of the connective tissue traversing the thin cell wall and intact cuticle in regions with protruding protoplasts. In addition, the sticky secretion produced from the glandularconnectives might also increase the efficiency of transport and pollen transfer. Taken together, these results show that each gland has a peculiar mechanism and type of secretion, suggesting additional levels of floral specialisation for interactions with pollinators. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: Floral glands; Histochemistry; Oil-collecting bees; Pollination; Ultrastructure